Analisis Kewenangan dan Tanggung Jawab Pemerintah Daerah dalam Menangani Aktivitas Bermain Layang-Layang di Jalan HKSN Berdasarkan Peraturan Daerah kota Banjarmasin Nomor 6 Tahun 2020 - Ahmad Redha; redha, Ahmad Redha (Journal of Society and Scientific Studies, 2026)
This study aims to analyze the authority and responsibility of the regional government in handling kite-flying activities on HKSN Street, Banjarmasin City, based on Regional Regulation Number 6 of 2020 concerning Public Order and Community Peace. Such activities often cause traffic safety disturbances and public disorder, requiring examination within the framework of regional autonomy. This research employs a normative legal method using statutory and conceptual approaches, focusing on the legal norms governing regional authority and the constitutional responsibility of the state. The results show that the regional government has a clear legal basis to prohibit activities endangering public safety under Article 15(2) of Regional Regulation No. 6/2020. However, its implementation remains suboptimal due to weak law enforcement, limited interagency coordination, and the absence of alternative recreational spaces. The study recommends strengthening coordination between the Transportation Agency, Civil Service Police Unit (Satpol PP), and the police, along with revising the regulation to include obligations for providing public recreation areas. A participatory approach based on good governance principles is essential to improve public legal awareness and ensure sustainable public order.